Overcoming the Myth of the Silent Woman and Double-Colonization in Ernest Hemingway’s Indian Camp - tahboun, abdelhafid (International Journal of Language and Literary Studies, 2023)
This paper explores the theme of overcoming the myth of the silent woman and double colonization in Ernest Hemingway’s Indian Camp (1924). It scrutinizes the subversive demolishment of double-minority status lifting the curtain on the thunderous screams of a female character as an emblem of expressive agency. To thematize this research topic and critically diagnose its feasible dimensions, this research paper casts the spotlight of analytical interpretation on the political dynamics, the implicit underpinnings and the insinuated textual unsaid underlying the female character of the Indian woman as a case study placed under scrutiny. To excavate in depth the ideological ramifications and the political implications tacitly embedded in the overall textual fabric of this literary artifact, this current study brings into play the postcolonial feminist perspective as a deconstructive paradigm through decomposing and dismantling a miscellany of excerpted extracts quoted from the decomposed text. This research paper selects relevant thematic insights that embody the counter-patriarchal upheaval and the defiant insurgency unravelling the notion of the Voice as a third space of self-revival, restorative replenishment of the Indian female subaltern and decision-making power. This research paper culminates in a wide array of clear-cut conclusions: A. The strategic reversal of the gender-exclusive model of grand narrative shifts it from misogynistic patriarchy and the top-bottom androcentric monopoly of power to a gender-inclusive vision of democratic parity, political enfranchisement and performative agency. B. The transformational metamorphosis in the tectonic plates of male-female asymmetrical power structures and the replacement of the hierarchically structured pyramid of man-woman relation by a harmonious continuum of gender complementarity. C. The counter-active shift drifts from the reductionistic mindscape of phallocentric discrimination to the anti-patriarchal philosophy of gynocentric perspective.